An unusual case of Kaposi sarcoma masquerading as cystitis in a kidney transplant recipient. Issue 5 (16th July 2019) - Nair, Vinay; Sheikh, Fatima; Hirschwerk, David; Fahmy, Ahmed; Bhaskaran, Madhu; Grodstein, Elliot; Winnick, Aaron; Maki, Robert; Teperman, Lewis; Molmenti, Ernesto
Abstract: Human Herpes Virus‐8 (HHV‐8) may reactivate in immunocompromised patients including recipients of solid organ transplants. Reactivation of HHV‐8 may result in Kaposi sarcoma (KS). KS typically occurs with dermatologic involvement but can affect virtually any other organ; most commonly the gastrointestinal tract. We present a diagnostically challenging case of KS in a South American woman 7 months after kidney transplant. She presented with recurrent urinary tract infection manifested by pelvic pain and dysuria. Imaging studies revealed bladder thickening with pelvic lymphadenopathy. Findings on tissue biopsied from the bladder and lymph nodes were consistent with KS. Her skin was not affected. This case illustrates that KS and other HHV‐8–related diseases should be on the differential diagnosis as a cause of mass lesions as well as lymphadenopathy in transplant recipients. The case exemplifies the need to pursue a tissue diagnosis in immunocompromised patients when a diagnosis is uncertain.